Work‐relatedness of carpal tunnel syndrome: Systematic review including meta‐analysis and GRADE. Issue 6 (2nd November 2022) - Hassan, Awa; Beumer, Annechien; Kuijer, P. Paul F. M.; van der Molen, Henk F.
Abstract: Background and Aims: Carpal tunnel syndrome (CTS) is the most common peripheral nerve entrapment syndrome with a high prevalence among workers. Insights on the physical work‐related risk factors is necessary to develop appropriate preventative methods. The objective of this systematic review, including meta‐analyses, is to assess which physical work‐related risk factors are associated with carpal tunnel syndrome. Methods: Systematic literature searches were carried out using PubMed and Embase until September 6, 2021. Studies were included if: (1) CTS was clinically assessed, (2) the studies were prospective cohort studies, and (3) the exposure was reported using terms of exposed/less or nonexposed. Risk of bias was assessed using the Quality in Prognosis Studies (QUIPS) tool. Quality of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE). Results: In total, 9270 patients with CTS from a population of 1, 051, 707 workers were included from 17 studies. Meta‐analyses revealed high‐quality evidence for associations between CTS and high exposures to repetition (hazard ratio [HR] 1.87, 95% CI 1.42–2.46), force intensity (HR 1.84, 95%CI 1.22–2.79), exposures above hand activity level of ACGIH (HR 1.75, 95%CI 1.40–2.17), and the Strain Index >10 (HR 1.58, 95% CI 1.09–2.30). No significant associations were found for pinch gripping, hand‐arm vibration or force duration. High computer‐use exposure was significantly associated with a decreased rate of work‐related CTS (HR 0.28, 95% CI 0.12–0.64). Conclusion: This systematic review of prospective cohort studies found high certainty for an increased rate of CTS due to a high Strain Index, exposures exceeding the Activity Level of ACGIH, and high force intensity and high repetition. Workers performing tasks requiring both high force and high repetition even have a higher rate of developing CTS.